Analisis Usability Pada Produk Smart Door Lock Menggunakan Metode Use Questionnaire - Nadia Putri Nilamsari; Ferida Yuamita (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2023)
Adisutjipto Angkasa High School in the laboratory has a fire risk and has some carbon content in the air which disturbs the respiratory system of the laboratory users. As for the manufacture of smart door lock products that have an important function value, namely as a tool for emergency needs when work accidents occur in the chemical laboratory and physics laboratory environment. The method used in this study is usability using the Use Questionnaire with validity and reliability measurements. The population in this study was 72 students of Angkasa Adisutjipto High School and the sample of this study was 41 students of Angkasa Adisutjipto High School. The results of this study show that the R value with df=39 and the correlation is significant at the 0.05 level and 2-tailend is 0.3081. reliability test results with a Cronbach's Alpha value of 0.756.